Marker Pen Lithography for Flexible and Curvilinear On‐Chip Energy Storage. (14th July 2015) - Jiang, Qiu; Kurra, Narendra; Alshareef, Husam N.
Abstract : On‐chip energy storage using microsupercapacitors can serve the dual role of supplementing batteries for pulse power delivery, and replacement of bulky electrolytic capacitors in ac‐line filtering applications. Despite complexity and processing costs, microfabrication techniques are being employed in fabricating a great variety of microsupercapacitor devices. Here, a simple, cost‐effective, and versatile strategy is proposed to fabricate flexible and curvilinear microsupercapacitors (MSCs). The protocol involves writing sacrificial ink patterns using commercial marker pens on rigid, flexible, and curvilinear substrates. It is shown that this process can be used in both lift‐off and etching modes, and the possibility of multistack design of active materials using simple pen lithography is demonstrated. As a prototype, this method is used to produce conducting polymer MSCs involving both poly(3, 4‐ethylenedioxythiophene), polyaniline, and metal oxide (MnO2 ) electrode materials. Typical values of energy density in the range of 5–11 mWh cm −3 at power densities of 1–6 W cm −3 are achieved, which is comparable to thin film batteries and superior to the carbon and metal oxide based microsupercapacitors reported in the literature. The simplicity and broad scope of this innovative strategy can open up new avenues for easy and scalable fabrication of a wide variety of on‐chip energy storage devices. Abstract : Marker pen ink is used for writing sacrificial patterns to fabricate energy storage devices on a variety of surfaces, including on‐chip, round, and curved surfaces, as micropower units capable of glowing a light‐emitting diode. This process can be used in both lift‐off and etching modes, and the possibility of multistack design of active materials using simple pen lithography is demonstrated.